2011
DOI: 10.1253/circj.cj-10-0186
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Stents vs. Bare Metal Stents in Saphenous Vein Graft Disease - Insights From a Meta-Analysis of 7,090 Patients -

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp rug-eluting stents (DES) are a major advance in interventional cardiology, but evidence in favor of their use in aortocoronary saphenous vein graft (SVG) disease, a common "off-label" indication for DES implantation in daily practice, is controversial. SVGs have a high occlusion rate 1,2 and percutaneous coronary intervention (PCI) with bare metal stent (BMS) implantation was the preferred treatment for SVG lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
1
12
0
1
Order By: Relevance
“…However, in this patient population, clear benefits from the use of drug-eluting stents in the reduction of death and myocardial infarction were not observed (Lupi et al, 2011).…”
Section: Meta-analysismentioning
confidence: 79%
See 3 more Smart Citations
“…However, in this patient population, clear benefits from the use of drug-eluting stents in the reduction of death and myocardial infarction were not observed (Lupi et al, 2011).…”
Section: Meta-analysismentioning
confidence: 79%
“…Saphenous vein graft disease represents the "Achilles heel" of coronary artery bypass surgery interventions, due to the high failure rate of saphenous vein grafts (Lupi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 They concluded that, in SVG disease, DES significantly reduced TVR, but they did not provide clear benefits on mortality and MI, with an opposite direction of the results for mortality observed from randomized and nonrandomized observational data.…”
Section: Article P 280mentioning
confidence: 98%